Mapping Actors and Power Relations Between Actors in Tourism Village Development - Sidiq, Rd. Siti Sofro; Indrawati, Indrawati; Marnelly, T Romi; Rosaliza, Mita; Ihsan, Muhammad; Sugiyanto, Seger (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
The coastal area of Sepahat village is known for its beach and mangrove ecotourism and is one of the priorities for tourism development in Bengkalis Regency. Institutional performance in developing the tourism sector and the creative economy is not yet optimal, characterized by a lack of membership management skills, formulating plans, overcoming problems and developing networks. In fact, tourism institutions and the creative economy are at the heart of optimizing existing potential. The aim of this research is to identify and analyze actor mapping and power relations between actors in the development of the Sepahat tourist village. The research results are expected to provide benefits from the academic side, namely in the form of textbooks and reference books related to the sociology of community empowerment, sustainable development and local wisdom. The realization of academic benefits is also carried out through publication of manuscripts in accredited journals so that they can provide references to various parties. The results of this research will produce and map actor interests, status, roles and relationships between actors which can be used as a mitigation document for institutional management to optimize the benefits of the Sepahat Tourism Village for the community.